2017
DOI: 10.3389/fnbeh.2017.00240
|View full text |Cite
|
Sign up to set email alerts
|

Immediate-Early Genes Modulation by Antipsychotics: Translational Implications for a Putative Gateway to Drug-Induced Long-Term Brain Changes

Abstract: An increasing amount of research aims at recognizing the molecular mechanisms involved in long-lasting brain architectural changes induced by antipsychotic treatments. Although both structural and functional modifications have been identified following acute antipsychotic administration in humans, currently there is scarce knowledge on the enduring consequences of these acute changes. New insights in immediate-early genes (IEGs) modulation following acute or chronic antipsychotic administration may help to fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 263 publications
2
20
0
Order By: Relevance
“…We found that an acute treatment with SEP-856 produced a marked elevation of a number of activity dependent genes (IEGs), such as Arc , c-Fos , Zif268/Egr1 and Npas4 , under basal conditions in the prefrontal cortex, and much less in other structures. In line with our data, IEGs expression throughout the brain in response to antipsychotic challenge has been extensively investigated showing region-specific modulations of IEGs expression after antipsychotic treatments [ 26 ]. Specifically, atypical antipsychotics such as clozapine induced limbic and prefrontal cortical IEGs expression, whereas a substantial induction in the striatum was found following haloperidol administration [ 27 ].…”
Section: Discussionsupporting
confidence: 83%
“…We found that an acute treatment with SEP-856 produced a marked elevation of a number of activity dependent genes (IEGs), such as Arc , c-Fos , Zif268/Egr1 and Npas4 , under basal conditions in the prefrontal cortex, and much less in other structures. In line with our data, IEGs expression throughout the brain in response to antipsychotic challenge has been extensively investigated showing region-specific modulations of IEGs expression after antipsychotic treatments [ 26 ]. Specifically, atypical antipsychotics such as clozapine induced limbic and prefrontal cortical IEGs expression, whereas a substantial induction in the striatum was found following haloperidol administration [ 27 ].…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, geneM21/isoM30 expression was negatively correlated with the degree of lifetime antipsychotic exposure in the subset of patients for whom these data were available (P=0.001, Pearson; Fig S11B). As such, it will be worthwhile to determine whether this module is a core driver of the therapeutic response, as has been suggested (65). Other neuronal modules distinguished SCZ and BD from ASD (Fig 5B), including geneM7, enriched for synaptic and metabolic processes with the splicing regulator NOVA2 (Fig 5C).…”
Section: Neuronal Isoform Network Capture Disease Specificitymentioning
confidence: 99%
“…The role of glycine neurotransmission in the modulation of Homer gene expression has been explored in reference to the action of antipsychotics, alone or with the adjunction of glycine B-site agonists such as D-cycloserine (187). Multiple lines of evidence suggest an involvement of Homer (long and short forms, and their splicing variants) in antipsychotics action at level of PSD (188)(189)(190)(191). Polese et al have shown how add-on Dcycloserine to typical (haloperidol) and atypical (clozapine) antipsychotic treatment, modulate the expression of Homer 1a, in a negative trend in caudate-putamen (187).…”
Section: Glycine Transporters and The Postsynaptic Densitymentioning
confidence: 99%